The influence of digital transformation on the total factor productivity of enterprises: The intermediate role of human-machine cooperation - Qi Xiong; Jingyi Yang; Xiuwu Zhang; Yarui Deng; Yao Gui; Xiaoyang Guo (Journal of Innovation & Knowledge (JIK), 2025)
Digital transformation acts as a stabilizer for corporate production efficiency and a catalyst for sustainable development. This paper provides digital transformation indicators at the enterprise level based on text analysis and uses listed companies in China from 2009 to 2021 as the research subject to explore the impact of digital transformation on the total factor productivity (TFP) and the dynamic mechanism of human–machine collaboration in its transmission process. The findings reveal that (1) digital transformation significantly enhances TFP, a conclusion that remains valid after considering endogeneity issues and conducting a series of robustness checks, thereby refuting the productivity paradox associated with digital transformation; (2) furthermore, the enabling effect of digital transformation on TFP varies significantly across enterprises due to differences in ownership, factor intensity, asset size, degree of marketization, tax preference, and geographical location; (3) in terms of the impact mechanism, digital transformation promotes TFP by enabling efficient human–machine collaboration patterns. This study not only complements research on the influencing factors of microenterprise TFP, providing empirical evidence for improving enterprise production efficiency, but also offers insights for local governments to formulate differentiated digital policies.
Keywords: D24; J24; L25; O33; 650; Digital transformation; Human-machine cooperation; Listed companies; Total factor productivity